DIVERSITY AND DENSITY OF MEGABENTHOS IN CORAL REEF ECOSYSTEMS IN KERA ISLAND WATERS, KUPANG DISTRICT, INDONESIA - Kangkan, Alexander L.; Sine, Kiik G.; Boik, Rini I. (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Kera Island belongs to the small islands of the East Nusa Tenggara with the potential conservation of coral reefs and various associated megabenthos organisms. This research aims to a) determine the diversity and density of megabenthos in coral reef ecosystems in Kera Island Waters, b) investigate the grouping between variables from environmental characteristics of megabenthos in coral reef ecosystems in Kera Island Waters, and c) observe the relationship between the diversity and density of megabenthos with the percentage of coral cover in Kera Island Waters. The research method used was a survey with direct measurements in the field. Megabenthos data was taken using the Benthos Belt Transect technique, while the coral cover was taken using the Underwater Photo Transect technique and analyzed using CPCe 4.1 software. The research data were then analyzed for density and percentage of megabenthos, diversity index value, (H’) Shannon, coral cover, organic matter, carbonate content, principal component analysis, and correlation. The study's results regarding the diversity index value of megabenthos in Kera Island Waters ranged from 0.796 to 1.631. The similarity of environmental parameters makes two main components. The first includes current velocity, organic content, dissolved oxygen, and depth; the second are carbonate content, TDS, temperature, and salinity characterize the second main component. The average organic matter was 8.32%, while the carbonate content was 50.09%. The coral reefs and megabenthos density had a robust relationship, with a correlation coefficient of 0.93.